Визначення сутності сільських територій - Павліха, Наталія Володимирівна; Хомюк, Наталія Леонідівна; Pavlikha, Nataliia V.; Khomiuk, Nataliia L. (My University, 2017)
В статті висвітлено різні підходи до сутності сільських територій. Виокремлено основні функції сільських територій. Розглянуто існуючі класифікації сільських територій. Узагальнено основні проблеми на сільських територіях. Розглянуто Концепцію розвитку сільських територій.

The article covers different approaches to the nature of rural areas. The main functions of rural areas are singled out. The existing classification of rural areas is considered. The main problems in rural areas are singled out. The concept of development of rural areas is considered.
Keywords: сільська територія; сільський розвиток; система; класифікація сільських територій; rural area; rural development; system; classification of rural areas